Spontaneous mutation 7B-1 in tomato impairs blue light-induced stomatal opening - Hlavinka, Jan; Nauš, Jan; Fellner, Martin (Plant science, 2013)
It was reported earlier that 7B-1 mutant in tomato (Solanum lycopersicum L.), an ABA overproducer, is defective in blue light (BL) signaling leading to BL-specific resistance to abiotic and biotic stresses. In this work, we examine responses of stomata to blue, red and white lights, fusicoccin, anion channel blockers (anthracene-9-carboxylic acid; 9-AC and niflumic acid; NIF) and ABA. Our results showed that the aperture of 7B-1 stomata does not increase in BL, suggesting that 7B-1 mutation impairs an element of BL signaling pathway involved in stomatal opening. Similar stomatal responses of 7B-1 and wild type (WT) to fusicoccin or 9-AC points out that activity of H(+)-ATPase and 9-AC-sensitive anion channels per se is not likely affected by the mutation. Since 9-AC restored stomatal opening of 7B-1 in BL, it seems that 9-AC and BL could block similar type of anion channels. The stomata of both genotypes did not respond to NIF neither in darkness nor in any light conditions tested. In light, 9-AC but not NIF restored stomatal opening inhibited by ABA in WT and 7B-1. We suggest that in comparison to WT, the activity of S-type anion channels in 7B-1 is more promoted by increased ABA content, and less reduced by BL, because of the mutant resistance to BL.
Keywords: Solanum lycopersicum; signální transdukce; Signal Transduction; světlo; Anthracenes; Chloride Channels; Plant Growth Regulators; mutace; Proton-Translocating ATPases; Genotype; Plant Stomata; Light; Darkness; anthraceny; rostlinné geny; Abscisic Acid; regulátory růstu rostlin; Genes, Plant; protonové ATPasy; rostlinné proteiny; chloridové kanály; Plant Proteins; genotyp; průduchy rostlin; kyselina abscisová; Mutation; tma